Rapid characterization of oxidative deterioration in edible oil by optical photospectrometry - More, Pravin S.; Shelke, Anil V.; Late, Dattatray J. (Journal of Food and Dairy Technology, 2015)
This research work aimed to investigate the kinetic reaction of reused cooking oil and find the optimum conditions of its process. The feedstock was collected from the commercially available sunflower oil. Our investigation shows that the kinetic reaction of reused sunflower oil (auto-oxidation) obtained in terms of variation of absorption coefficient of unexposed sunflower as 0.05 while the exposed sunflower had 0.075. The optimum condition from optical absorption spectroscopy investigations were obtained as 0.267 for unexposed sunflower oil and 0.194 for exposed sunflower oil at room temperature. Furthermore, our FTIR spectroscopic results obtained are accurate and precise enough for such detection such as free fatty acid (FFA ~ 26%), acid ~ 53% and saponification ~ 192% get reduce in exposed oil was investigated.